Neuroendocrine Regulation of Tumor-Associated Immune Cells - Colon-Echevarria, Claudia B.; Lamboy-Caraballo, Rocio; Aquino-Acevedo, Alexandra N.; Armaiz-Pena, Guillermo N. (Frontiers in Oncology, 2019)
Mounting preclinical and clinical evidence continues to support a role for the neuroendocrine system in the modulation of tumor biology and progression. Several studies have shown data supporting a link between chronic stress and cancer progression. Dysregulation of the sympathetic nervous system (SNS) and the hypothalamic-pituitary-adrenal (HPA) axis has been implicated in promoting angiogenesis, tumor cell proliferation and survival, alteration of the immune response and exacerbating inflammatory networks in the tumor microenvironment. Here, we review how SNS and HPA dysregulation contributes to disturbances in immune cell populations, modifies cancer biology, and impacts immunotherapy response. We also highlight several interventions aimed at circumventing the adverse effects stress has on cancer patients.